Validation of a telephone‐based administration of the simplified nutritional appetite questionnaire - Binh Duong Thai; Jürgen M. Bauer; Annette Eidam; Jane Durga; Stefan Grund; Thomas Mross; Petra Benzinger (Wiley, 2023)
Abstract Background Anorexia of aging is characterized by an age‐associated reduction of appetite, whose aetiology in most cases is multifactorial and which often triggers malnutrition. The Simplified Nutritional Appetite Questionnaire (SNAQ) is an established screening tool. This study aimed to investigate reliability, validity, and feasibility of its telephone administration (T‐SNAQ) in German community‐dwelling older adults. Methods This cross‐sectional single‐centre study recruited participants from April 2021 to September 2021. First, the SNAQ was translated into German according to an established methodology. After translation, reliability, construct validity, and feasibility of the T‐SNAQ were analysed. A convenience sample of community‐dwelling older adults aged ≥70 years was recruited. The following measurements were applied to all participants: T‐SNAQ, Mini Nutritional Assessment - Short Form (MNA‐SF), six‐item Katz index of independence in activities of daily living (ADL), eight‐item Lawton instrumental activities of daily living (IADL), telephone Montreal Cognitive Assessment (T‐MoCA); FRAIL scale, Geriatric Depression Scale (GDS‐15) and Charlson co‐morbidity index as well as daily caloric and protein intake. Results One hundred twenty participants (59.2% female) with a mean age of 78.0 ± 5.8 years were included in the present study. The percentage of participants identified with poor appetite based on T‐SNAQ was 20.8% (n = 25). T‐SNAQ showed a good internal reliability with a Cronbach's alpha coefficient of 0.64 and a good test-retest reliability [intraclass coefficient of 0.95 (P < 0.05)]. Regarding construct validity, T‐SNAQ was significantly positively correlated with MNA‐SF (r = 0.213), T‐MoCA (r = 0.225), daily energy (r = 0.222) and protein intake (r = 0.252) (P < 0.05). It also demonstrated a significant negative association with GDS‐15 (r = −0.361), FRAIL scale (r = −0.203) and Charlson co‐morbidity index (r = −0.272). Regarding applicability, the mean time for T‐SNAQ was 95 s and completion rate was 100%. Conclusions The T‐SNAQ is a feasible screening instrument for anorexia of aging in community‐dwelling older adults via telephone interviews.